A Foucauldian Discourse Analysis on News Reports Addressing High School Student Enrolment Zoning Policy - Arima Renny Dayu Putri; Markus Budiraharjo (JETL (Journal of Education, Teaching and Learning), 2020)
Empirical studies drawn from a Foucauldian discourse analysis suggest the complexity of policy implementations. Policy construction and implementation involve a set of different stakeholders, causing many competing agendas from different bodies to interfere with the processes and making policy outcomes highly unpredictable. This study was set to investigate how high school student enrolment zoning policy in Indonesia was represented in major online daily journals, specifically during the two months of June and July 2019. The latest enrolment zoning policy has been considered to be too disruptive among both parents and schools. Utilizing a discourse analysis, this paper attempted to reveal what issues were addressed and what agendas or powers were contested. In this discourse analysis, it is found that the three online journals as the resources of the study were not strong enough in presenting the news. All of them have not discussed the student’s aspect as the implementer of the zoning policy.